NFC2BLE Communications’ Bridge: From Flash to Continuous Monitoring of Biological Parameters - Vicente, Jose Maria; Avila-Navarro, Ernesto; Rodriguez-Martinez, Alberto; de la Casa Lillo, Miguel Angel; Sabater-Navarro, Jose Maria (Elektronika ir Elektrotechnika, 2020)
The devices for monitoring biological variables have become a hot topic in the last years. An important aspect in the design of these wearable devices is the continuous communication, as well as the associated energy consumption. As a result, the concept of flash monitoring has been recently coined. This implies that the reading of the variables is not made in a continuous manner, but the values are stored on the sensor electronics for a while and then retrieved altogether to the reader. This concept reduces the energy consumption since there is no continuous communication, and this feature is, therefore, beneficial in certain contexts. However, the communication is sometimes required to be continuous, so that solutions based on continuous communication or alarms can be implemented. This work shows a technological development that allows converting a biological variable reading system based on flash monitoring into a continuous one. The details of the electronic development of the components are shown, and the software structure integrated in the microcontroller is discussed. The system devoted to the management and remote acquisition of the data is shown as well. As an example, the performance of the system is shown in two different contexts: with a flash biopatch for the body temperature monitoring designed in the laboratory and with a commercially available flash interstitial glucose monitoring system.